2014
DOI: 10.1177/1527476414525241
|View full text |Cite
|
Sign up to set email alerts
|

Playboring in the Tester Pit

Abstract: The labor of video game testers has barely registered within political-economic analyses of work practices in the game industry. This article addresses this gap through a critical deployment of the concept of precarity and its multiform nature experienced by game testers. Drawing on Harry Braverman’s concept of “degradation of labor,” I aim to contribute to media labor literature by introducing the concept of “degradation of fun,” where testers are alienated from play and forced to develop instrumental and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The work of external testers bears similarities to that of testers based directly in development studios, from a shared hope in starting a career in the industry through QA to experiencing precarity due to the project-based organization of work (see Bulut 2015). Nonetheless, outsourced testers' experiences of work insecurity and instability were amplified by the structure of the outsourcing business model.…”
Section: Working Conditions In Outsourced Testing: Enduring Precaritymentioning
confidence: 99%
See 2 more Smart Citations
“…The work of external testers bears similarities to that of testers based directly in development studios, from a shared hope in starting a career in the industry through QA to experiencing precarity due to the project-based organization of work (see Bulut 2015). Nonetheless, outsourced testers' experiences of work insecurity and instability were amplified by the structure of the outsourcing business model.…”
Section: Working Conditions In Outsourced Testing: Enduring Precaritymentioning
confidence: 99%
“…Like their counterparts in development studios (Bulut 2015), outsourced testers' work is quantified to measure their proficiency in finding and reporting errors in software. Quantification of testers' labor results in increased competition in the work environment, with interviewees suggesting that the most productive testers gain greater work security and protection from redundancy.…”
Section: Working Conditions In Outsourced Testing: Enduring Precaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Those at the lower end of the pay scale have less power to negotiate and less protection. A North American qualitative study argued that game testers are 'precarious workers' and pay is kept low due to the high demand for these positions and the perception that this job is a route into the industry (Bulut, 2015). My own research into community managers in the games industry in Ireland found that while these positions demand significant gaming and cultural knowledge, job advertisements rarely give remuneration details -indeed, some interviewees informed me that their employment contracts forbid them from discussing their remuneration (Kerr, 2016).…”
Section: The Passion Precarity and Crunch Of Game Workmentioning
confidence: 99%
“…Given the rapid rise of the commercial Web and its increasing concentration in large monopoly players such as Google and Facebook, it is no surprise that we have seen a resurging interest in studying the political economy of the Internet. Various studies engage with the conditions and labor practices of digital media industries, ranging from games (e.g., Bulut, 2015;Kücklich, 2005;Deuze, et al, 2007), to Web development (e.g., Neff, et al, 2005;Kennedy, 2012;Ross, 2003), to the high-technology manufacturing plants in free trade zones across the developing world (e.g., Dyer-Witheford, 2015;Qiu, et al, 2014;Sandoval, 2013). Such studies often emphasize the relative under-compensation of digital media industries, including for white-collar, middle-class, and creative work.…”
Section: Analyzing the Internet Economymentioning
confidence: 99%